2016
DOI: 10.1007/s11207-016-0916-z
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Quiet-Sun Hard X-Rays Related to Solar Wind Superhalo Electrons

Abstract: In this paper, we propose that the accelerated electrons in the quiet Sun could collide with the solar atmosphere to emit Hard X-rays (HXRs) via non-thermal bremsstrahlung, while some of these electrons would move upwards and escape into the interplanetary medium, to form a superhalo electron population measured in the solar wind. After considering the electron energy loss due to Coulomb collisions and the ambipolar electrostatic potential, we find that the sources of the superhalo could only occur high in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Our observations of numerous microjets in quiet-Sun regions might be consistent with the results of Wang et al (2016), who suggested interchange reconnection as the coronal source of superhalo electrons (Wang et al 2012). Specifically, they proposed that small-scale interchange reconnections in quiet-Sun regions produce an upward-traveling population of accelerated electrons, which could escape into the interplanetary space and form the superhalo electrons measured in the solar wind.…”
Section: Chen Et Al 2020)supporting
confidence: 91%
“…Our observations of numerous microjets in quiet-Sun regions might be consistent with the results of Wang et al (2016), who suggested interchange reconnection as the coronal source of superhalo electrons (Wang et al 2012). Specifically, they proposed that small-scale interchange reconnections in quiet-Sun regions produce an upward-traveling population of accelerated electrons, which could escape into the interplanetary space and form the superhalo electrons measured in the solar wind.…”
Section: Chen Et Al 2020)supporting
confidence: 91%
“…By comparison, Krucker et al (2007), who analyzed much larger (typically M class) flares, found a ratio of ≈ 0.2%. On the other hand, based on simulations, Wang et al (2016) estimate that, in the quiet Sun, the ratio of electrons propagating outwards to form the solar wind superhalo to those that could potentially propagate downwards and produce HXR emission can be as high as 30 %.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies provide conflicting evidence regarding where in situ electrons are energized compared to their HXRemitting counterparts. In certain flares, for example, emerging flux or interchange reconnection (e.g., Heyvaerts et al 1977;Wang et al 2016;Battaglia et al 2023) 2011; Musset et al 2020) may ultimately allow loop-top electrons to escape, while having access to hot, over-dense material usually related to HXR-emitting electrons. Alternatively, or in conjunction, the presence of a turbulent acceleration mechanism (e.g., Kontar et al 2017a;Stores et al 2021) may both heat the surrounding plasma and energize electrons simultaneously.…”
Section: Summary and Discussionmentioning
confidence: 99%